Current Trends in Annual Historical Re-Enactments Events in Catalonia. Uses of Cultural Heritage - Antonio Rojas Rabaneda (EXARC, 2019)
The project “Re-enactments events in Catalonia” seeks to identify and analyse annually occurring events that make use of cultural heritage and history for the purposes of tourism, economic promotion and dissemination, and for other festive, recreational or educational ends. The activity programmes of all active events currently held in Catalonia were analysed and quantitative data provided in order to facilitate evaluation of their role in tourism and in promoting cultural heritage. The research was overseen by the Projects and Communication Unit of the Catalan Institute for Cultural Heritage Research (ICRPC) and performed within the framework of the Cultural Heritage of Catalonia research group. Preconsolidated Research Group (GRPRE) (2017 SGR 835).